Automatic will enabled system of multi-modal operation - Karim, Md. Risul; Waliullah, Syed Shaiyan Kamran; Kamal, Badruddin; Rhaman, Md. Khalilur; Khan, Mumit; Jamil, Insan Arafat (© 2013 IEEE, 2016)
This conference paper was presented in the 2nd International Conference on Informatics, Electronics and Vision, ICIEV 2013; Dhaka; Bangladesh; 17 May 2013 through 18 May 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICIEV.2013.6572674